2023
DOI: 10.1021/acsnano.2c06727
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Ultrafast Lattice Distortions during Exciton–Polaron Formation in Lead Halide Perovskite Nanocrystals

Abstract: The microscopic origin of slow hot-carrier cooling in lead halide perovskites remains debated and has direct implications for applications. Slow hot-carrier cooling of several picoseconds has been attributed to either polaron formation or a hot-phonon bottleneck effect at high excited carrier densities (>1018 cm–3). These effects cannot be unambiguously disentangled with optical experiments alone. However, they can be distinguished by direct observations of ultrafast lattice dynamics, as these effects are expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 78 publications
2
19
0
Order By: Relevance
“…53 Mechanistically it is relevant to compare the observed behavior in MAPbI 3 NCs with that of CsPbBr 3 NCs, previously reported in the literature. 11,19,54 Analogous experiments on CsPbBr 3 NCs by Kirschner et al identified a photoinduced distortion attributed to an orthorhombic to cubic transition, distinct from a strictly thermal phase transition in that it bypassed the tetragonal phase and the reverse cubic to orthorhombic transition occurred at a much higher temperature than the orthorhombic thermal transition. 11 More recently, Cannelli et al found using transient Xray absorption spectroscopy (XAS) that a polaronic distortion is likely responsible for much of the structural rearrangement in CsPbBr 3 .…”
Section: Resultsmentioning
confidence: 87%
“…53 Mechanistically it is relevant to compare the observed behavior in MAPbI 3 NCs with that of CsPbBr 3 NCs, previously reported in the literature. 11,19,54 Analogous experiments on CsPbBr 3 NCs by Kirschner et al identified a photoinduced distortion attributed to an orthorhombic to cubic transition, distinct from a strictly thermal phase transition in that it bypassed the tetragonal phase and the reverse cubic to orthorhombic transition occurred at a much higher temperature than the orthorhombic thermal transition. 11 More recently, Cannelli et al found using transient Xray absorption spectroscopy (XAS) that a polaronic distortion is likely responsible for much of the structural rearrangement in CsPbBr 3 .…”
Section: Resultsmentioning
confidence: 87%
“…To fully explain our observations, a noncharging model including multiexcitonic states needs to be invoked. Trapped excitons (TEs), in which the electron–hole pairs are localized and stabilized by the lattice polarons, have been proposed in CsPbBr 3 perovskites. , In our SCPQDs, given the softness of the surface lattices and the strong exciton–surface interaction promoted by the size confinement, we propose that exciton–surface lattice polarons can form, which leads to TE formation.…”
mentioning
confidence: 90%
“…Accordingly, the dynamic screening picture in LHPs is incomplete, and its microscopic mechanism continues to be debated (27,28). Furthermore, identifying and characterizing polaronic behavior is experimentally difficult (26,(28)(29)(30)(31)(32). Optical Kerr effect (OKE) in LHPs (33,34) did not succeed in unveiling a lattice response and can be explained by an instantaneous electronic polarization (due to hyperpolarizability) instead (35).…”
Section: Introductionmentioning
confidence: 99%